Using language sample analyses across English dialects: A case-based approach for preschoolers. - Kokotek, Leslie E.; Washington, Karla N.; Bazzocchi, Nicole (Clinical Linguistics & Phonetics)
This study compared language samples from typically developing 4-year-olds who spoke African American English (AAE), Jamaican English (JE), or Mainstream American English (MAE) to assess the value of using language sample analysis (LSA) measures for characterising language use across dialects of English. Specific LSA metrics included mean length of utterance (MLU) in morphemes and in words, the Index of Productive Syntax (IPSyn), Developmental Sentence Scoring (DSS) and measures of lexical diversity. Children demonstrated diverse linguistic patterns across dialects, but a Kruskal–Wallis H test did not reveal significant differences in scores obtained through LSA measures. Notably, the IPSyn captured morphosyntactic structures in each category across dialects where prior research has highlighted limitations. This preliminary study uses a case-based approach to illustrate the applicability of LSAs in describing linguistic variations across children who speak different dialects of English. Moreover, the findings from this study underscore the potential use of LSAs in describing linguistic patterns to support the characterisation of communication profiles for culturally and linguistically diverse children.